Contesting Concepts, Imagining New Possibilities: David Graeber, Democracy, and Social Studies Curriculum - Nelson, Peter M. (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
This essay places David Graeber’s consistent focus on imagination and possibilities into conversation with social studies education. In a sociopolitical climate characterized by neoliberalism, militarized borders, and political censorship of social studies teaching and learning in P-12 schools, it is crucial that social studies teachers and teacher educators in the United States, Canada, and elsewhere continue to engage in pedagogies that are critical and responsive, providing students with representations of the past and present that, rather than reproducing the status quo, playfully imagine alternative futures that are more equitable, just, and free. Building from Graeber’s work in direct civic action, this essay offers ideas for how standardized social studies concepts can be reconfigured in affecting, life-giving ways.